INSTUDY OF CONSTRUCTION OF OSEANIC GILLS NETWORK TOOLS IN KARIMUN DISTRICT RIAU ISLANDS PROVINCE - Teguh Afriyanto; Alit Hindri Yani; Polaris Nasution (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis research was conducted on July 25, 2017 in Karimun Regency, Riau Islands Province. This study aims to find out about the material and construction of oceanic fishing gear. The method used in this study is a survey. The type of gill nets used are oceanic gill nets to be discussed. The characteristics of the net are examined and compared with ordinary gill nets. Oceanic fishing gears are almost the same as ordinary gill nets. It's just that what distinguishes this oceanic net fishing gear from ordinary nets is the size of the ship, the type of net and the size of the mesh size and area of operation. Whereas for the construction part such as buoy, ballast, lever, upper rope, lower rope, and leash are basically the same as ordinary gill nets. Keywords: Construction, Oceanic Nets, Karimun.